New Strain of Yersinia enterocolitica Pathogenic for Rodents - Carter, Philip B. (1973)
A strain of Yersinia enterocolitica, biotype 2, serotype 8, isolated from the blood of a human patient has been found to be highly pathogenic for rodents.